1995
DOI: 10.1017/s0022112095000280
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated flows past a rigid sphere or a spherical bubble. Part 1. Steady straining flow

Abstract: This work reports the first part of a series of numerical simulations carried out in order to improve knowledge of the forces acting on a sphere embedded in accelerated flows at finite Reynolds number, Re. Among these forces added mass and history effects are particularly important in order to determine accurately particle and bubble trajectories in real flows. To compute these hydrodynamic forces and more generally to study spatially or temporally accelerated flows around a sphere, the full Navier–Stokes equa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
239
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 337 publications
(262 citation statements)
references
References 22 publications
21
239
0
2
Order By: Relevance
“…20,28 -30 Extensive tests on the accuracy of the simulation technique have been performed and documented. 20,31 Results on spectral decay at various points within the computational domain, sensitivity to grid resolution, and detailed comparison with prior simulations and ex- 18 Good agreement is also observed with the numerical results obtained by Mittal 32 and Magnaudet et al 33 The effect of domain size was investigated by doubling the size of the computational domain to 60 times the particle radius. The mean drag coefficient obtained for the case of a linear shear flow varied by less than 0.02% and the corresponding change in mean lift was even smaller.…”
Section: Methodssupporting
confidence: 52%
“…20,28 -30 Extensive tests on the accuracy of the simulation technique have been performed and documented. 20,31 Results on spectral decay at various points within the computational domain, sensitivity to grid resolution, and detailed comparison with prior simulations and ex- 18 Good agreement is also observed with the numerical results obtained by Mittal 32 and Magnaudet et al 33 The effect of domain size was investigated by doubling the size of the computational domain to 60 times the particle radius. The mean drag coefficient obtained for the case of a linear shear flow varied by less than 0.02% and the corresponding change in mean lift was even smaller.…”
Section: Methodssupporting
confidence: 52%
“…For spherical bubbles, the added-mass coefficient C M is known to be constant and equal to 1 2 whatever the Reynolds number. [21][22][23] The drag coefficient C D depends on the instantaneous bubble Reynolds number Re p =2͉v − u͉R / . As we are mostly concerned with bubble Reynolds numbers in the range 0.1-10, we select a C D correlation based on results obtained in direct numerical simulations with Re p Ͻ 50, namely 23…”
Section: -4mentioning
confidence: 99%
“…In the above expression, the drag coefficient C D depends on the instantaneous bubble Reynolds number Re p =2͉v − u͉R / ͑ being the kinematic viscosity of the carrying fluid͒. Based on direct numerical simulations around a single bubble, 30 32 showed that the history force may be neglected for moderate accelerations of the bubble at such high Re p . The added-mass coefficient C M is now known to be constant and equal to 1 / 2 whatever the Reynolds number.…”
Section: A Lagrangian Trackingmentioning
confidence: 99%